Pengaruh Kepemimpinan Kepala Sekolah Terhadap Motivasi Kerja Guru SDK Waitabula - Karolus Wulla Rato; Marselinus Arianto Malo; Apliana Kartini Zangga; Arman Bili; Feriati Holo (Asosiasi Riset Ilmu Teknik Indonesia, 2024)
The influence of the principal's leadership on teacher work motivation (Waitabula Elementary School) The influence of the Principal's leadership on teacher work at Waitabula Elementary School. This research aims to determine the description of teachers' work at SDK Waitabula and the relationship between teachers and the leadership of the school principal. This research is quantitative research. Meanwhile, based on the source, this research uses primary data, namely data collected by the researcher himself through distributing questionnaires to respondents, in this case is teachers at Waitabula Elementary School with a total of 36 respondents. The data collection method uses a questionnaire with a measurement scale and data obtained by descriptive statistical analysis. Data processing was carried out using SPSS version 20. Based on the research results, it showed that the school principal's leadership was in the high category with descriptive analysis results of 95% and the teacher's work was also in the high category with a percentage of 100%. The principal's leadership and teacher work motivation have a very strong relationship. The correlation coefficient value is 0.823 and the style applied by the principal at Waitabula Elementary School is the influence of leadership.